Tax Revenues Determinants: Empirical Study Based on World, Regional, and Income Levels of Data - Suparna Wijaya; Jamil Prayer (Budapest International Research and Critics University, 2022)
Tax revenue in many countries is influenced by many factors. Many research had been done to determine which factors affect tax revenue with different data sample. This research contribution is to complete them. By using panel data of 134 countriesfrom 2002 to 2018 this research analyze the impact of share of agriculture in GDP, share of industry in GDP, share of service in GDP, per capita income, inflation rate, exchange rate, trade opennes, urban population, government effectiveness, political stability, quality of regulation, control of corruption, rule of law, and voice and accountability to tax revenue. This research also uses another panel data model based on different regional and income classifications. The result is that in overall countries model, all variables except inflation rate and control of corruption have significant effect to tax revenue. Different results also found in different models based on regional and income classification.